Enhanced Efficiency of Tandem Organic Light‐Emitting Diodes via Manipulating Heterojunction Composition of Charge Generation Unit. Issue 17 (17th July 2021) - Lü, Zhaoyue; Zhang, Lijiang; Wang, Junling; Xiao, Jing
Abstract : Tandem organic light‐emitting diodes (OLEDs) with an organic photovoltaic heterojunction (OPV‐HJ) as a charge generation unit (CGU), consisting of fullerence (C60 ) and copper phthalocyanine (CuPc), are fabricated. The device structures are ITO/EL unit/C60 –CuPc HJ/MoO3 /EL unit/Al, where EL unit is composed of NPB/Alq3 /LiF. The efficiency improvement of tandem OLEDs is achieved by manipulating the structure and composition of C60 –CuPc HJs. The charge generation and transport characteristics of CGUs are strongly dependent on the detailed structures of C60 –CuPc HJs and the optimized CGU is 0.5:1 C60 :CuPc bulk‐HJ. The improved efficiency of the tandem device with 0.5:1 C60 :CuPc bulk‐HJ as CGU demonstrates to be the result of better charge carrier balance induced by the optimal charge transport and charge generation of C60 :CuPc bulk‐HJs according to their surface morphology and absorption spectra. These results shed light on that C60 :CuPc OPV‐HJ‐based CGU is a promising connection unit for the fabrication of high‐efficiency tandem OLEDs. Abstract : The effect of various heterojunctions (HJs) of C60 –CuPc as charge generation unit is investigated. When the ratio of bulk‐HJ is optimal (C60 :CuPc = 0.5:1), the performance of tandem device is best, which is mainly attributed to an increase in both C60 –CuPc interfacial area and absorption in 0.5:1 C60 :CuPc bulk‐HJ.